CRAFTING EFFECTIVE PAUD TEACHING MODULES: A TRAINING NEEDS ASSESSMENT FOR POSYANDU CADRES IN BANDUNG - Kristiyanti, Lilis; Nurhayati, Sri (Jurnal Visi Ilmu Pendidikan, 2024)
This paper aims to investigate the training needs of Posyandu cadres in Bandung City for the effective development and delivery of Early Childhood Education (PAUD) programs. The research method involved conducting extensive interviews with cadres to gather insights into their perspectives and challenges. Data collection revealed that cadres recognize the pivotal role of teaching modules and emphasize the importance of religious and moral values in early childhood education. They expressed a commitment to adaptability and improvement while facing resource challenges. The results highlight cadres' dedication to providing interactive and engaging educational content and their willingness to receive training and support for module development. These findings have implications for enhancing the quality of early childhood education in Bandung City by focusing on specialized training, resource allocation, knowledge sharing, research-based assessments, community engagement, and alignment with national education goals. Addressing these needs will contribute to the holistic development of young children in the region.